Ammonia volatilization from composting with oxidized biochar. Issue 6 (1st November 2020) - Hestrin, Rachel; Enders, Akio; Lehmann, Johannes
Abstract: Animal manure, agricultural residues, and other sources of biomass can be diverted from the waste stream and composted into valuable fertilizer. However, composting often results in substantial N loss through NH3 gas volatilization. We investigated biochar's capacity to improve NH3 –N retention during composting of poultry manure and straw. After 7 wk, total N loss from composting with unoxidized biochar was twofold and sixfold higher than N loss from composting with oxidized biochar and without biochar (307, 142, and 51 mg N g −1 N in the initial compost feedstocks, respectively). When cumulative NH3 –N loss was calculated relative to CO2 –C loss to account for differences in microbial activity, NH3 –N/CO2 –C loss from compost with oxidized biochar was 55% lower than from compost with unoxidized biochar (82% lower based on mass balance). Oxidized biochar particles removed from compost after 7 wk retained 16.0 mg N g −1 biochar, compared with only 6.1 mg N g −1 retained by unoxidized biochar, suggesting that N retention by biochar particles provides a mechanism for reduced NH3 –N loss. These data show that oxidized biochar enhanced microbial activity, doubled composting rate, and reduced NH3 –N loss compared with unoxidized biochar and that biochar's physiochemical characteristics modulate its performance in compost. In particular, the presence of oxidized surface functional groups, which can be increased artificially or through environmental weathering, appear to play an important role in key compost processes. This has implications for other natural and managed systems where pyrogenic organic matter may mediate biological activity and nutrient cycles.